Nanotechnology Fundamentals Applied to Clinical Infectious Diseases and Public Health. (20th November 2021) - Tobin, Ellis; Brenner, Sara
Abstract: Nanotechnology involves the discovery and fabrication of nanoscale materials possessing unique physicochemical properties that are being employed in industry and medicine. Infectious Diseases clinicians and public health scientists utilize nanotechnology applications to diagnose, treat, and prevent infectious diseases. However, fundamental principles of nanotechnology are often presented in technical formats that presuppose an advanced knowledge of chemistry, physics, and engineering, thereby limiting the clinician's grasp of the underlying science. While nanoscience is technically complex, it need not be out of reach of the clinical practitioner. The aim of this review is to introduce fundamental principles of nanotechnology in an accessible format, describe examples of current clinical infectious diseases and public health applications, and provide a foundation that will aid understanding of and appreciation for this burgeoning and important field of science.